PENGARUH TINGKAT KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM PENGRAJIN SONGKET DI KOTA PALEMBANG - Syaharah, Delsi Puja; Widyanti, Yeni (JURNAL ILMIAH EDUNOMIKA, 2024)
The purpose of this study is to test hypotheses and produce empirical evidence regarding the effect of tax socialization, service quality and knowledge level of taxpayers compliance. This study used a sampel of 69 respondents. Respondents in this study were the UMKM Songket taxprayers in Palembang City. Data were analyzed using multiple linear regression analysis method with the help of SPSS program.The results of this study indicate that partially increase socialitazion has no effect on taxprayer compliance, while the service quality and level of taxprayer knowledge partially have a significant effect on taxprayer compliance. Simultaneously socialization of tax service quality and level of knowledge of taxpayers has a significant effect on taxpayer compliance. Keywords : Taxpayer Compliance, Tax Socialization, Service Quality, Taxpayer Knowledge Level